Alcohol Effects on Colon Epithelium are Time‐Dependent. (22nd July 2019) - Bishehsari, Faraz; Zhang, Lijuan; Voigt, Robin M.; Maltby, Natalie; Semsarieh, Bita; Zorub, Eyas; Shaikh, Maliha; Wilber, Sherry; Armstrong, Andrew R.; Mirbagheri, Seyed Sina; Preite, Nailliw Z.; Song, Peter; et al.
Abstract : Background: Alcohol intake increases the risk of developing colon cancer. Circadian disruption promotes alcohol's effect on colon carcinogenesis through unknown mechanisms. Alcohol's metabolites induce DNA damage, an early step in carcinogenesis. We assessed the effect of time of alcohol consumption on markers of tissue damage in the colonic epithelium. Methods: Mice were treated by alcohol or phosphate‐buffered saline (PBS), at 4‐hour intervals for 3 days, and their colons were analyzed for (i) proliferation (Ki67) and antiapoptosis (Bcl‐2) markers, (ii) DNA damage (γ‐H2AX), and (iii) the major acetaldehyde (AcH)–DNA adduct, N 2 ‐ethylidene‐dG. To model circadian disruption, mice were shifted once weekly for 12 h and then were sacrificed at 4‐hour intervals. Samples of mice with a dysfunctional molecular clock were analyzed. The dynamics of DNA damage repair from AcH treatment as well as role of xeroderma pigmentosum, complementation group A (XPA) in their repair were studied in vitro. Results: Proliferation and survival of colonic epithelium have daily rhythmicity. Alcohol induced colonic epithelium proliferation in a time‐dependent manner, with a stronger effect during the light/rest period. Alcohol‐associated DNA damage also occurred more when alcohol was given at light. Levels of DNA adduct did not vary by time, suggesting rather lower repair efficiency during the light versus dark. XPA gene expression, a key excision repair gene, was time‐dependent, peaking at the beginning of the dark. XPA knockout colon epithelial cells were inefficient in repair of the DNA damage induced by alcohol's metabolite. Conclusions: Time of day of alcohol intake may be an important determinant of colon tissue damage and carcinogenicity. Abstract : Alcohol consumption increases the risk of colon cancer. Circadian disruption promotes alcohol's effect on colon carcinogenesis. Here we show that alcohol effect on carcinogenesis markers such as proliferation and DNA damage is time dependent, coupled to the diurnal variations in the excision repair gene expression in colon. We conclude that alcohol‐induced epithelial damage in the colon appears to be time dependent, and in part could be explained by the temporal variation of the epithelial repair capacity.